The Protesting Body in the Social Movements Against COVID-19 Restrictions: Looking Into the Visual Protest Repertoires - Zhen Sun; Wei Luo (SAGE Open)
Drawing on Deleuze and Guattari’s theory of body and assemblage, this article examines the body-self of the anti-new normal protesters during the COVID-19 pandemic. It focuses on the expressive and material components that constitute the anti-new normal protest events that occurred in several countries during the first half of 2020 and further explores the forces or lines of life that produce the distinct bodies of the protesters. The initial qualitative content analysis of the visual protest repertoires generates three levels of themes, which reveal the primary constituent elements of the expressive assemblages of the anti-new normal protest and articulate the protesters’ demands, fears, anger, and imaginative relations. A further discussion and interpretation within Deleuze and Guattari’s conceptual framework illuminate how the protesters’ bodies become a territory where biological/physical and socio-cultural forces contend with one another; in other words, how the assemblages of enunciations temporarily capture the body of the protesters.